2016
DOI: 10.17795/jjnpp-38798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hibiscus sabdariffa L. Extract and Enalapril with Regard to Their Effect on Lung Fibrosis in a Bleomycin-induced Rat Model of Lung Fibrosis

Abstract: Background: Pulmonary fibrosis is an idiopathic and chronic inflammatory interstitial lung disease that responds only weakly to available medical therapies and has a potentially fatal prognosis. Hibiscus sabdariffa L. contains several antioxidants, such as protocatechuic acid (PCA) and anthocyanins, which may be beneficial for the treatment of fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Protective effects of M. oleifera on lung functions, hematological damage, and lipid damage induced by heavy metals have been demonstrated using experimental rats. Ameliorative effects of H. sabdariffa on pulmonary fibrosis and chronic inflammatory interstitial lung disease have also been studied using rats exposed to a toxic chemical (Hemmeti et al 2016, Ajibade et al 2021. It has been demonstrated that pre-treatment using Z. officinale extract improves lung function and normalizes lung injuries in alcoholic humans and rats exposed to polychlorinated biphenyls (Alireza et al 2017, Ahd et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of M. oleifera on lung functions, hematological damage, and lipid damage induced by heavy metals have been demonstrated using experimental rats. Ameliorative effects of H. sabdariffa on pulmonary fibrosis and chronic inflammatory interstitial lung disease have also been studied using rats exposed to a toxic chemical (Hemmeti et al 2016, Ajibade et al 2021. It has been demonstrated that pre-treatment using Z. officinale extract improves lung function and normalizes lung injuries in alcoholic humans and rats exposed to polychlorinated biphenyls (Alireza et al 2017, Ahd et al 2019.…”
Section: Discussionmentioning
confidence: 99%